Assessment of Factors Militating Against Agricultural Science Practical in Secondary Schools in Kwara State, Nigeria - Ibrahim Oba (Indonesian Journal of Science and Education, 2024)
This study assessed the factors militating against agricultural science practical in secondary schools in Kwara State, Nigeria. A descriptive survey research design was used, and a sample of 478 agricultural science teachers was selected using multistage sampling techniques. Five research questions were raised and answered while five null hypotheses were formulated and tested at 5% level of significance. Data was collected through a self-developed questionnaire and analysed using frequency count, percentage, mean, and Pearson-Product Moment Correlation. The findings revealed that insufficient human resources, negative attitudes of learners, limited time, financial resources, and inadequate infrastructure were significant challenges impeding the successful implementation of agricultural science practical in secondary schools. The study recommends among others that government should prioritize the recruitment of qualified and experienced agricultural science teachers to teach agricultural science practical in secondary schools.